Response of a plate to PZT actuators - ZOU, Dingguo; CROCKER, Malcolm J. (Archives of Acoustics, 2009)
In this paper, the response of a plate with arbitrary boundary conditions to PZT actuators is derived. It is assumed that the plate and the actuators are rectangular and the edges of the PZT actuators are parallel to the respective edges of the plate. The response of the plate is decomposed into normal modes. The modal amplitude of the normal mode is represented in terms of the shape function of the actuator and the normal mode. The shape function of the actuator is given as a~singularity function. The normal modes for the boundary conditions with which we are concerned are calculated based on theoretical analyses of Magrab. The results of this paper are useful in designing an active noise control system in which the PZT actuators are used as the control sources.